Ikrar Halal: Solusi Muhammadiyah untuk Usaha Mikro dan Kecil dalam Memenuhi Kewajiban Sertifikasi Halal - Sopa, Sopa; Maskufa, Maskufa (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum, 2024)
The obligation of Halal certification mandated by the Law of Halal Product Assurance (Undang-Undang Jaminan Produk Halal or UUJHP) No. 34 2014 for businesses is felt burdensome, especially by small and medium enterprises (SMEs). This research focuses on service process provided by a division in Muhammadiyah organization called “Ikrar Halal Muhammadiyah” or IHM as a solution offered by Muhammadiyah to solve the problem. Data were collected through observation and documents. Observation was conducted through participation in a discussion meeting held by Lembaga Pemeriksa Halal dan Kajian Halalan Thayiban (LPHKHT) Muhammadiyah (the Muhammadiyah Institute for Halal Investigation and Halalan Thayiban Studies) and Majelis Tarjih dan Tajdid (MTT) Muhammadiyah (the Muhammadiyah Tarjih and Tajdid Council). Furthermore, data from documents were collected from related parties such as Halal Center Perguruan Tinggi Muhamadiyah-Aisyiyah (HCPTMA) or the Halal Center of Muhammadiyah-Aisyiyah College, LPHKHT and MTT. The result of the research shows that IHM offered by Muhammadiyah is a smart solution helping the SMEs in fulfilling the halal certification obligation which is implemented gradually. IHM is not a halal certificate per se, but it is a halal self-declaration of SMEs about their products. This self-declaration is conducted under Muhammadiyah’s supervision through the involvement of HCPTMA, LPHKHT and MTT. When the SMEs are considered to be capable, they will be guided to propose the halal certification process held by BPJPH which requires more complex process than IHM. IHM is sort of a breakthrough step to fill legal vacuum and an ijtihad of Muhammadiyah.